Improving the success of InsurTech opportunities. (2018) - Bruce, D.; Avis, C.; Byrne, M.; Gosrani, V.; Lim, Z.; Manning, J.; Popovic, D.; Purcell, R.; Qin, W.
Abstract: The Working Party has produced this report in order to prompt readers to engage at an early stage in InsurTech projects, through considering (i) the full range of risks associated with InsurTech developments, (ii) the lifecycle of an InsurTech venture and how any risk considerations may vary over this lifecycle and (iii) the extent to which InsurTech ventures align with risk strategy and risk appetite. The report contains practical guidance for actuaries, risk professionals, insurance companies and their Boards on these considerations, and can be used to facilitate appropriate questioning, to help ensure that InsurTech-related business decisions are fully cognisant of the risk management issues and to help ensure the success of projects. The Working Party developed this guidance having carried out an industry survey on a number of risk management topics relating to InsurTech, as well as having carried out interviews with a number of relevant senior stakeholders across the insurance industry, in order to better understand current sentiment and how risk management plays a part when considering opportunities in InsurTech. The Working Party views on the findings from these activities are summarised in the report.